Dr. Ebadat Brelvi’s Unpublished Letters To Dr. Moeen-Ud-Din Aqeel - Dr. Sikandar Hayat; Bazghah Qandeel (Zaban-o-Adab, 2023)
Dr. Ebadat Brelvi is regarded as a multi-oriented figure of literature and an asset of incomparable value. This article introduces Dr. Ebadat Brelvi ’s seven unpublished letters for the first time ever. These letters address well-Known researchers Dr.Moeen -Ud-Din Aqeel. At the end of the article comprises of explanatory notes regarding those letters. It would make the discernment and connotations of these letters easily comprehendible. These letters would hold the pedestal of a tectonic, substantial and historical allusion after the publication of this article. .